PENGELOLAAN PERTAMBANGAN MINERAL BATUAN SETELAH TERBITNYA UNDANG-UNDANG 23 TAHUN 2014 OLEH PEMERINTAH KABUPATEN KUDUS JURNAL Disusun - Andrea Yudhistira; Soewanto Adhi; Dzunuwanus Ghulam Manar (Journal of Politic and Government Studies, 2016)
This research was conducted in order to identify Management of Rocks Mineral Mining after publication of Regulation 2014 number 23 by Kudus Regional Government. The withdrawal of mining management authority in Regulation 2014 number 23 led to various problems in regional government. It suffer loss on withdrawal of mining management authority. This research identity and explains response of Kudus Regional Government with limited authority to minimize further losses.This research used qualitative method descriptive which data are collected and expressed in form of descriptive sentences. Subjects of this research were office of mineral mining rock (BPESDM) Kudus, Central Java office of Energy and Mineral Resources, and community around the mine. Data collection techniques included interviews, documentation, and literature and then analyzed through data reduction techniques, editing, data presentation and conclusion.The results concluded that Kudus Regional Government has only limited authority on minning management of its competence, such action in form of organizing, directing, implementing, and controlling. For future reference, The law must be more stuctured and orderly to prevent overlaping regulation.